2013
DOI: 10.1111/j.1525-1446.2012.01041.x
|View full text |Cite
|
Sign up to set email alerts
|

Heavy and Light/Moderate Smoking Among Building Trades Construction Workers

Abstract: Addressing the influence of these factors on heavy smoking could lead to the development of targeted, multiple components in comprehensive cessation strategies for blue-collar smokers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 63 publications
2
15
0
Order By: Relevance
“…M0 macrophages were reported to be inversely associated with patients' outcomes in various, such as adrenal cortical carcinoma and lung cancer [46,47]. Nowadays, majority studies evaluated the degree of smoking based on the frequency of tobacco use to define heavy smokers and light smokers without uniform quantifying standards [48][49][50]. Moreover, these cut-offs cannot accurately identify the true degree of smoking because they do not comprehensively consider the DNA damage and microenvironment alteration.…”
Section: Discussionmentioning
confidence: 99%
“…M0 macrophages were reported to be inversely associated with patients' outcomes in various, such as adrenal cortical carcinoma and lung cancer [46,47]. Nowadays, majority studies evaluated the degree of smoking based on the frequency of tobacco use to define heavy smokers and light smokers without uniform quantifying standards [48][49][50]. Moreover, these cut-offs cannot accurately identify the true degree of smoking because they do not comprehensively consider the DNA damage and microenvironment alteration.…”
Section: Discussionmentioning
confidence: 99%
“…[172829] These findings supports previously conducted studies involving multiple interventions in the workplace seetings. [3031]…”
Section: Discussionmentioning
confidence: 99%
“…Yet whilst Papadopoulos et al's (2010) work focused on the changing work environment within all industries, more focused research also lends support to the argument that construction work has considerable negative impacts on its workers' health, beyond the more tangible hazards it demands they regularly face on sites. For example, research in the US (Chin et al 2012) found that construction workers are almost twice as likely as the general working population to smoke, and they smoke more. Although this was also associated with sociodemographic characteristics such as age, male gender, lower levels of education and income, it was found to link to social pressures and stressful work, and higher exposure to occupational hazards.…”
Section: Public Health: the Symptomsmentioning
confidence: 99%